Pengolahan Daun Ketapang untuk Membantu Perekonomian dimasa Pandemi Covid-19 - I Komang Agus Sutiyasa (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
Ketapang leaf (Terminalia catappa L.) is one of the potentials of the Nusa Dua coastal area which currently has promising economic value. However, nowadays many people do not know how to process ketapang leaves, which usually only turn into garbage so that they can have economic value. This activity aims to introduce and help the community to take advantage of the potential of sea ketapang leaves (Terminalia catappa L.) to be processed into creative products in the form of processed ketapang leaves and ketapang leaf extract which can be used for ornamental betta fish (Betta sp.) So that they can have economic value and can help the community's economy during the Covid-19 Pandemic. In addition, with this activity, the community is expected to be able to take advantage of the potential of ketapang laut leaves not only during the pandemic but will continue when the situation normalizes and become a new business for people other than the tourism sector which is already well known in this area.